An inventory model for deteriorating products under preservation technology with time-dependent quality demand. Issue 1 (31st December 2023) - Sindhuja, S.; Arathi, P.
Abstract: In many real-world inventory deterioration concerns, the rate of deterioration of individual commodities is based on the deteriorating items during the storage period. Inventory models for degrading commodities have become more important in the food production sectors due to the unpredictability of product life spans. This deterioration can be overcome by involving a preservation factor to reduce the effects of decaying objects. This model is applicable for food production, in particular, dairy product (ice cream) suppliers to make inventory decisions in the inventory system under the effect of optimal values. In this paper, a preservative-based inventory model for deteriorating products with quality demand is discussed. The proposed model with cost functions yields the best operating plan and total sales. The policy combinations for dairy products are generally designed to reduce the deterioration rate, the expenditures, and the total cost. To illustrate the value of the proposed model numerical examples involving three flavours of ice creams have been studied. The model was tested with the real-time data obtained from the ice cream factory. Also, the proposed model's numerical results are compared with the existing model. Further, the sensitivity analysis is performed to study the effect of changes in different parameters of the model. The complex algebraic equations are solved using MATLAB R2013a.